How Gendhing Gamelan reduced anxiety in pregnancy - Djohan, Dr; Tyasrinestu, Fortuna; Sittiprapaporn, Phakkharawat (Asian Journal of Medical Sciences, 2020)
Background: Listening to music will not only have a soothing and uplifting effects on someone but also a positive influence on the unborn baby. The positive vibes that will be acquired from listening to music will create a prenatal stimulation that will help pregnant mother to bond with their unborn baby. It will enable them to lower their stress and anxiety levels and also reduce any stress that the unborn baby may feel in the womb. Previous researches claimed the ability of music, especially western music, in reducing anxiety and stress toward pregnant woman. Aims and Objective: Instead of using western music, the present study investigated the effect of listening to gamelan music toward the reducing of anxiety on pregnancy. Materials and Methods: In a pilot experiment, 60 healthy volunteers (mean age = 29.0; SD = 5.0) evaluated their anxiety responses to a Javanese traditional musical piece using a Slendro Sanga scale. Results: The research shows significant effect (p<0.05; F=5.340) of Javanese traditional music to reduce anxiety in pregnant woman thus the hypotheses are accepted. Conclusion: Trust toward pregnant woman is important to be built because it can be the foundation of self-confidence and preventing stress. That is why, external situation is important since it has impact in internal situation.